2017
DOI: 10.29015/cerem.513
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency decomposed – The case of Ugandan referral hospitals

Abstract: Abstract:Aim: In an audit report provided to the Ugandan Parliament by the Office of the Audit General, Uganda, technical efficiency in Ugandan referral hospitals was measured and analysed. The audit report pointed out that there was a relatively low level of technical inefficiency, at least in comparison with other African countries. The purpose of this study is to look further into the issue of why there is inefficiency. Design / Research methods:We use a Data Envelopment Analysis framework and decompose lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Similarly in a study to estimate the efficiency of public health dispensaries in Kenya, Bundi (2018) found that 41% were inefficient with average VRS efficiency at 70%, the CRS and scale efficiencies averaged 55% and 80% respectively. In another technical efficiency study of referral health facilities in Uganda, Mulumba et al (2017) indicate that long-run inefficiency varied overtime and more than 50 percent of the inefficiencies that were observed are related to scale factors. The study recommended that inefficient health units should use efficient ones as benchmarks or role models to improve their efficiency.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly in a study to estimate the efficiency of public health dispensaries in Kenya, Bundi (2018) found that 41% were inefficient with average VRS efficiency at 70%, the CRS and scale efficiencies averaged 55% and 80% respectively. In another technical efficiency study of referral health facilities in Uganda, Mulumba et al (2017) indicate that long-run inefficiency varied overtime and more than 50 percent of the inefficiencies that were observed are related to scale factors. The study recommended that inefficient health units should use efficient ones as benchmarks or role models to improve their efficiency.…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, the analysis explores efficiency only in a general sense using ratio indicators and ignores other factor inputs such as operational budget, essential medicines and health supplies (drugs), medical and non-medical staff used by health centres in the production of health outputs. In addition there are limited recently published health facility efficiency studies in Uganda (Mujasi et al, 2016;Mulumba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Congestion measured using either decomposition ( 9) or ( 11) is the most important source of inefficiency at the sample level in at least eight articles we are aware of: and Byrnes, Färe, Grosskopf, and Lovell (1988) both analyse US surface coal mines, Ç akmak and Zaim (1992), Wu, Devadoss, and Lu (2003) and Zhengfei and Oude Lansink (2003) assess Turkish, American and Dutch agriculture respectively, Färe, Grosskopf, and Pasurka (1989) analyse US electric utilities, Mulumba, Nalubanga, Nankanja, Manasseh, Månsson, and Hollén (2017) assess Ugandan referral hospitals, and Odeck (2006) evaluates the Norwegian public bus companies. Just to offer some basic idea of the amount of waste involved, Table 1 summarises for each study the average amount of congestion efficiency as well as its incidence (% of sample).…”
Section: Congestion Measurement: Amounts and Incidence Reported In The Empirical Literaturementioning
confidence: 99%
“…Finally, reanalysing data on the Chinese automobile and textile industries in the period 1981-1997, Flegg and Allen (2009a) obtain in an intertemporal analysis that congestion is critical for both sectors in a single year over this time horizon (1989 and 1995 for automobile and textile industries respectively). Mulumba, Nalubanga, Nankanja, Manasseh, Månsson, and Hollén (2017) report that for the year 2012 congestion dominates for 5 out of 13 observations. Nasierowski and Arcelus (2003) find that the innovation system in about 30% of countries suffers from congestion and that it is a dominant source for some of these countries.…”
Section: Congestion Measurement: Amounts and Incidence Reported In The Empirical Literaturementioning
confidence: 99%